The Problem of Science and Religion Correlation in the Christian Apologetics of S.S. Glagolev - Igor Pecheranskyy (Cхід, 2013)
The article reveals the main apologetical features in the studies of Sergiy Glagolev (1865-1937), the professor of Moscow Religious Academy. He was an representative of orthodox spiritual-academic philosophy. His works remain unknown till our days. Having analyzed the articles of that time Orthodoxical periodicals by Sergey Glagolev we concluded that the main characteristic was his approach to the science and religious problem's solving. He used evolutional theories of late XІX-th - the beginning of the XX-th centuries and attempts of "scientific substantiation of religious grounds"